2018
DOI: 10.1038/s41419-018-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

HOXA4, down-regulated in lung cancer, inhibits the growth, motility and invasion of lung cancer cells

Abstract: The involvement of HOXA4 in colorectal cancer and epithelial ovarian cancer has been reported. Although it has been reported that the Hoxa4 gene is involved in the patterning of the mouse lung during embryonic development, little is known about the biological functions of HOXA4 in lung cancer. In the current study, HOXA4 expression was down-regulated in lung cancer tissues when compared with non-cancerous tissues. HOXA4 expression was associated with tumor size, TNM stage, lymph node metastasis and prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…HOXA4 (Homeobox A4) belongs to the Homeobox gene family of transcription factors associated with cell differentiation and embryonic development control . HOXA4 regulation seems to associate with lung cancer cell proliferation, migration, and invasion in vitro and in vivo, besides poor prognosis in patients . We identified that the inferred regulatory unit of HOXA4 is enriched with differentially expressed genes and its activity was suppressed in tumor tissues compared to control tissues.…”
Section: Discussionmentioning
confidence: 92%
“…HOXA4 (Homeobox A4) belongs to the Homeobox gene family of transcription factors associated with cell differentiation and embryonic development control . HOXA4 regulation seems to associate with lung cancer cell proliferation, migration, and invasion in vitro and in vivo, besides poor prognosis in patients . We identified that the inferred regulatory unit of HOXA4 is enriched with differentially expressed genes and its activity was suppressed in tumor tissues compared to control tissues.…”
Section: Discussionmentioning
confidence: 92%
“…Wnt signaling induces ß-catenin translocation to the nucleus to form the ß-catenin/T-cell factor transcriptional activator which activates a number of target genes including survivin, cyclin D1, c-Myc and VEGF. The elevated expression of Wnt/ß-catenin downstream effectors then enhances cell proliferation [34][35][36] . Sustained-hypoxia-induced cancer progression via Wnt/ß-catenin signaling has been reported in various cancers including lung, liver, kidney and bladder [37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor regulates the related biological processes by binding to the 5 -flanking sequence of the coding region with various affinities. HOXA4 is associated with various cancer types and its downregulation leads to inhibition of growth and invasion of lung cancer cells (Cheng et al, 2018). Based on molecular analyses, the HOXA4 (c.920A>C:p.H307P) mutation may acquire pathogenicity by disrupting the DNA binding process during the early embryonic period and thus inhibit development of auricle cartilage.…”
Section: Discussionmentioning
confidence: 99%